KEWIRAUSAHAAN HIJAU: Tantangan dan Peluang dalam Pembangunan Ekonomi Ramah Lingkungan - Faza Auliana Zein; Evelyn Riahta; Keisya Genia Meisharini; Kherenz Natasha Olivia Tarigan; Harry Z. Soeratin (Veteran Economics, Management, & Accounting Review, 2025)
This research examines the challenges and opportunities in developing green entrepreneurship in Indonesia. In the Indonesian context, the potential for green entrepreneurship is enormous considering the wealth of natural resources and the need for sustainable solutions. However, challenges such as high initial costs, suboptimal regulations and low market awareness are still the main obstacles. On the other hand, the opportunities presented by the international market for environmentally friendly products, the renewable energy sector and organic farming open up huge opportunities for green entrepreneurs. With support from governments, financial institutions, and collaboration between sectors, green entrepreneurship can play an important role in building a more sustainable and inclusive economy Keywords: Green entrepreneurship, sustainable economy, environmentally friendly innovation, renewable energy   Abstrak  Penelitian ini mengkaji tantangan dan peluang dalam pengembangan kewirausahaan hijau di Indonesia. Dalam konteks Indonesia, potensi kewirausahaan hijau sangat besar mengingat kekayaan sumber daya alam dan kebutuhan akan solusi berkelanjutan. Namun, tantangan seperti biaya awal yang tinggi, regulasi yang belum optimal, serta rendahnya kesadaran pasar masih menjadi hambatan utama. Di sisi lain, peluang yang dihadirkan oleh pasar internasional untuk produk ramah lingkungan, sektor energi terbarukan, dan pertanian organik membuka kesempatan besar bagi wirausahawan hijau. Dengan dukungan pemerintah, lembaga keuangan, serta kolaborasi antar sektor, kewirausahaan hijau dapat memainkan peran penting dalam membangun ekonomi yang lebih berkelanjutan dan inklusif.  Kata Kunci: Kewirausahaan hijau, ekonomi berkelanjutan, inovasi ramah lingkungan, energi terbarukan